2003
DOI: 10.1038/sj.bjp.0705202
|View full text |Cite
|
Sign up to set email alerts
|

Despite increased plasma concentration, inflammation reduces potency of calcium channel antagonists due to lower binding to the rat heart

Abstract: 1 Rheumatoid arthritis reduces verapamil oral clearance thereby increases plasma concentration of the drug. This coincides with reduced drug effects through an unknown mechanism. 2 The effect of interferon-induced acute inflammation on the pharmacokinetics and electrocardiogram of verapamil (20 mg kg À1 , p.o.) and nifedipine (0.1 mg kg À1 , i.v.) was studied in SpragueDawley rats. 3 The effect of both acute and chronic inflammation on radioligand binding to cardiac L-type calcium channels was also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 46 publications
(59 reference statements)
2
45
0
Order By: Relevance
“…Pre-AA significantly elevated C max and AUC 0 -4 h for both enantiomers of verapamil (Table 1). Similar effects have been observed in acute inflammation (Laethem et al, 1994;Sattari et al, 2003) and confirm that pre-AA is a suitable alternative model of inflammation for pharmacokinetic studies. It is of value to mention that, following oral administration to inflamed rats, a greater extent of variability was observed in the plasma verapamil concentrations (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Pre-AA significantly elevated C max and AUC 0 -4 h for both enantiomers of verapamil (Table 1). Similar effects have been observed in acute inflammation (Laethem et al, 1994;Sattari et al, 2003) and confirm that pre-AA is a suitable alternative model of inflammation for pharmacokinetic studies. It is of value to mention that, following oral administration to inflamed rats, a greater extent of variability was observed in the plasma verapamil concentrations (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Other models of inflammation have shown varying effect on protein binding of verapamil. Endotoxininduced inflammation reduces unbound fraction of verapamil (Laethem et al, 1994), whereas interferon ␣-2a-induced inflammation does not significantly affect protein binding (Sattari et al, 2003). This suggests that altered protein levels may be dependent on the type of inflammation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Down-regulation of hepatic P-gp in AA rats was attributed to elevated levels of cytokines such as TNF-and IL-6 but not IL-1 (Philippe et al, 1997). Similarly, increased plasma concentrations of drugs in AA rats correlated with increased serum TNF-level (Sattari et al, 2003). Several in vitro and in vivo studies have shown up-regulation of NF-κB in RA and osteoarthritis (Handel et al, 1995;Mor et al, 2005).…”
Section: Mechanisms Of Altered Drug Metabolism In Ramentioning
confidence: 93%
“…Based on these early observations, recent studies have also shown altered PK of methotrexate, T-5557 (novel anti-inflammatory agent) and doxorubicin in AA animals (Achira et al, 2002a(Achira et al, , 2002b2002d). Although, a significant increase in the plasma concentrations of verapamil in rats and humans with underlying arthritis were reported, there were no changes in the PD of verapamil (prolongation of PR interval) (Mayo et al, 2000;Sattari et al, 2003). This discrepancy was then attributed to a decrease in the receptorligand affinity in inflammation (Laporte et al, 1998;Shore et al, 1997).…”
Section: Pk/pd Studiesmentioning
confidence: 97%